Work pressure of the administrative and academic members of Biskra University, its sources and its relation to some personal and functional variables - ضيف, احمد; موفق, سهام; طوال, هيبة (Journal of Economics and Administrative Sciences, 2019)
The study aimed to highlight the reality of the functional pressures with its dimensions (role ambiguity, role conflict, role burden, glass ceiling, and discrimination in composition). The researchers also relied on the questionnaire as a essential tool for data collection. The field study was conducted at the University of Mohammed Khiedr - Biskra -, the study was conducted on the basis of the total survey, which included all the workers of the 6 faculties of Biskra University (523 female employees).     After the analyzing of the data using the version 21 of the statistical program Spss, The study reached a number of results, the most of them is the low level of the functional pressures of the university employees in their different dimensions